Attitudes and preferences toward the adoption of voice-controlled intelligent personal assistants: Evidence from Croatia - Biloš, Antun; Budimir, Bruno; Kraljević, Borna (Information Research an international electronic journal, 2023)
Purpose. The primary goal of this paper was to explore the current level of voice-controlled intelligent personal assistant (IPA) adoption in a non-English speaking European country. This relatively novel technology exhibited immense growth in recent years, both on smartphones and as standalone devices with yet insufficiently explored usage patterns and implications associated with the internet of things (IoT) concept. Design/methodology/approach. The main research focus was set on attitudes and perceptions of users and non-users related to benefits and barriers of IPA adoption, privacy and security issues, trust as well as mobile phone usage patterns, motivators, and associated smartphone digital literacy. The research was conducted on a sample (N=310) of Croatian mobile phone users utilizing an online survey and an adopted research framework. Findings. Based on the collected data, the adoption rate of IPA was generally low but present, nevertheless. IPA users tend to use such devices for fun and convenience, utilizing its hands-free capabilities along with personalized tasks and information-seeking options. In contrast, IPA non-users suggested that the main barriers to IPA adoption were low perceived usefulness and functionality issues in addition to lack of usage habit and related lack of experience. Originality/value. This paper provides an examination of the differences between IPA users and non-users as well as an overview of (non-)user perception related to privacy and security issues associated with IPA and trust in companies’ appropriate use of IPA-generated data.